Pemikiran Ki Hadjar Dewantara dan Implikasinya Bagi Sekolah di Era Industri 5.0 - Fitri, Karina Rahmah; Kuswandi, Dedi; Wedi, Agus (Universitas Pahlawan Tuanku Tambusai, 2025)
This article aims to examine the thoughts of Ki Hadjar Dewantara through the Systematic Literature Review (SLR) approach and its implications in the development of education in the Industry 5.0 era. Ki Hadjar Dewantara, an Indonesian education figure who emphasizes the concept of